Vigilância em saúde: perfil dos trabalhadores assistidos em unidade básica de saúde - Mendes, Amanda Cristina De Oliveira (2023)
Introduction - Worker's Health is part of Collective Health and aims at the treatment and rehabilitation of injuries, the promotion and protection of workers' health and the reduction of morbidity and mortality. Knowing that the gateway to user health care is in Primary Health Care, through Basic Family Health Units, interest in listening to the perspectives of these worker users was awakened. Objectives - To understand the reason that leads the working population enrolled in a territory to seek care at Basic Family Health Units; describe the sociodemographic profile of the population of workers enrolled in a territory; evaluate the sociodemographic profile and the perception of the population of users/workers enrolled in a territory and identify the social profile and access characteristics of users of a Basic Family Health Unit. Methodology - This research is a master's thesis presented as equivalent work in the form of two articles. Both are studies with a quantitative approach, descriptive in terms of objectives, and bibliographic and field studies in terms of procedures. An online questionnaire was applied to users of a Basic Family Health Unit. In article 1, people aged between 18 and 69 years old, user-workers who agreed to participate in the research were considered as inclusion criteria, totaling a sample of 103 participants. In product 2, the inclusion criteria were over 18 years old who consented to the Free and Informed Consent Form, with a sample of 122 participants. Results – Two articles were generated, one published in FOCO Magazine and the other submitted in Higeya Magazine. Among the 122 participants, it was observed that the employed population 98 (80.3%) is four times larger than the unemployed population 24 (19.7%). The predominance of 87 (71.3%) of the participants were female biological sex, 37 (30.3%) aged between 40 and 49 years and with predominant employment relationship 33 (36.9%) in the Consolidation of Labor Laws . In addition, it is noted that the majority 59 (60.2.0%) seek the UBSF for vaccination and 50 (51.0%) for medical care. However, 52 (53.1%) of the user-workers reported having some chronic illness and/or condition that requires medical follow-up. When analyzing the users' perception, 67 (68.4%) of the interviewees recognized that it was important to seek the UBSF without being sick, 86 (87.8%) considered participation in disease prevention groups to be important and decisive, but only 18 ( 18.4%) of these interviewees stated that they had already participated in operative groups in a basic health unit. It was noticed that the participants who work seek the UBSF Marta Helena more, annually, in a preventive way 66 (54.1%), than those who do not work. And those who do not work seek the UBSF in more curative conditions 81 (66.6%), when they feel pain or discomfort. Another important data regarding access is that 68 (66.0%) reported knowing the opening hours of the Unit, but 35 (33.9%) pointed out as an aggravating factor the incompatibility of hours between attendance and work. Conclusion – It was possible to understand that the factors that lead user-workers to seek care at the UBSF are the health promotion and disease prevention resources. However, the non-working population still has healing characteristics, seeking the UBSF in situations of illness. Among the characteristics that hinder access to the UBSF is the incompatibility of schedules between work and care, thus requiring better management of schedules, providing greater coverage of care.